Nationalitet og Kirke i Danmark og Slesvig-Holsten i 1770-1920 med særligt henblik på Grundtvigs betydning - Thyssen, A. Pontoppidan (Grundtvig-Studier, 1999)
Nationality and Church in Denmark and Schleswig-Holstein with special reference to the importance of N.F.S. Grundtvig By Anders Pontoppidan Thyssen Introduction A feature common to the Scandinavian countries is the Lutheran, State-church heritage which resulted in widespread spiritual uniformity. But in the 18th century and particularly after 1770, the »enlightenment« prepared the way for a freer public debate, which formed the background of the numerous movements of the 19th century, representing different opinions. Prominent among them, are the national and religious movements which were closely related since they concerned the society as a whole and became of great importance for the political and cultural development of the people. The following survey of these lines of development must therefore begin the with the Age of Enlightenment which, in particular, brought up the crucial national question of the relationship between Danish and German, and it may have its natural conclusion with the year 1920 when this question was largely solved with the union of Northern Schleswig with Denmark. The aim of the first chapter about the years 1770-1815, however, is to give only a brief description of the »enlightenment« as a basis for the discussion of the much stronger national tensions that arose from about 1815 and continued along the same lines right up to 1920. The area that is dealt with is three of the mainlands of the old Danish monarchy, viz. the actual Denmark or the »Kingdom« (the islands and Northern Jutland down to Kolding Fiord) and the duchies of Schlewig and Holstein (from Kolding Fiord to the Elbe). The main emphasis will be on the Kingdom and the Northern, mainly Danish-speaking Schleswig (now called Southern Jutland), and thus also on Grundtvig as the most important representative of Danishness. But the duchies of Schlewig and Holstein also play a significant role, however, as the bearer of the strong German element. Chapter 1 It is especially Henrich Ussing’s great work on » Kirkeforfatningen i de kongelige danske stater« (The Church Government in the States of the Danish Monarchy, 6 vols., 1786-89) that throws light on the thinking of the Age of Enlightenment. It does not only deal with church government, but also treats questions of principle concerning state and social organization. The relationship between Danish and German is not discussed, but Ussing recommends the use of the vernacular everywhere as a prerequisite for understanding, especially in the church service. His exposition, however, is based primarily on natural law, understood as a rational social organization, whose laws aim at the »benefit and happiness common to all men«. The monarchy does not escape criticism; Ussing would prefer the power of the King to be re-stricted »by some amount of democracy«, i.e. through the establishment of Assemblies of the Estates. But since there is no prospect of such change in the near future, he recommends the gentle Danish monarchy as the best possible form of government. As a matter of fact Ussing went further than that in proposing a cooperation between the Government and enlightened citizens. He envisioned complete freedom of the press, and a free debate about important laws and decrees. These should be published, and the public should be encouraged to speak their minds and should be rewarded for the best contributions to the debate. He thus anticipated the political-liberal and national development up to the 1840s. In the following, the history of Danish nationality is briefly outlined. There was a reaction against the growing number of German immigrants, and at the same time a Danish national consciousness grew up, represented in the 1740s by Ludvig Holberg and other university academics. But opinions were divided. Tyge Rothe, a young Danish academic, claimed that the birthplace was insignificant, since the fatherland is the place where one works for the common good (1759). But a young lawyer composed a sharp refutation of this view, claiming the birthplace was all-important, since the natives would harbour a far more natural fervour and a deeper love for the country of their birth. The animosity against the Germans reached its peak in the time of J.F. Struensee (1770-72). Though bom in Halle, he arrogated complete power to himself in Copenhagen as the Queen’s lover. After that, he was able to exercise full control in all matters through Cabinet decrees in German until he was removed from office in February 1772 by a coup which led to his execution. The policies pursued by those in power after Struensee were consciously Danish and conserva-tive. The language of command in the army became Danish, and the old State Council was reestablished, now consisting of 6 members, 5 of whom were of Danish birth (February 1772). The power was concentrated round Ove Guldberg, whose national disposition appears from the Citizenship Act. It decreed that »all offices in Our states« should be reserved for »the native children of the Land«. But numerous celebrations and literary tributes demonstrate that in Denmark it was understood as a national victory that would benefit Danish citizens. But the Guldberg administration, too, came to an abrupt end when Crown Prince Frederik (Frederik VI) came of age and preferred to find his support in the German upper class which used to be the power basis. In reality A. P. Bemstorff came to be the actual head of government, and he arranged for the employment of numerous relatives and German friends in the government offices - regardless of the Citizenship Act. On the other hand Danish criticism was again very much in evidence. Briefly, it was to the effect that the Germans were strangers who relished the Danish bread, but despised Danish culture and the Danish language. It developed into a veritable Danish-German »feud«, especially in the years 1789-1790. Though there were few rejoinders from the Germans, the conflict probably contributed to a hostile attitude on both sides. There is little evidence available of the attitude in church circles to the national development. It does appear, however, that the clergy reacted strongly against Struensee, and at an officially decreed thanksgiving service after his fall, otherwise level-headed clergymen allowed themselves »to be carried away into passionate fury«. Many clergymen shared the enthusiasm over the Citizenship Act as a great national advance. Bishop Rottbøll, for example, asked in his speech at a celebration in Viborg what might not be expected now from a noble people like the Danish, »now that they have once again come to think of themselves as a people«. National feelings ran high, too, in the years 1800-1814, because of war and threats of war. Thus the Curate H.G. Clausen (later Arch-deacon) used strong words about »the defence of the fatherland« as the most important civic virtue. But by and large it seems that Danish clergymen were as a rule reluctant to participate in anti-German attacks, and this may be due to a certain amount of sympathy for German theology. Numerous Scandinavian students went to the University of Göttingen to learn more about modem theology and Bible exegesis. Among them was N.E. Balle, who made such a favourable impression that he was offered a university post in Germany. He preferred Copenhagen, however, where he be-came Bishop in 1783. Another theologian who was to some extent German-oriented, was Chr. Bastholm, who began as a pastor to a German congregation in Smyrna, but from 1772 became Copenhagen’s most »modem« preacher. He came to influence many clergymen, among them L.N. Fallesen, who published the first Theological Journal in Denmark (1793-1809). For a large part its contents were translations from the German. In the 1790s there was a tendency for many »enlightened« people to move to the left, launching direct attacks on Christianity as well as clergymen. Balle became known for countering such attacks with well-attended Bible readings in Frue Kirke. When they were printed, they attracted 36,000 subscribers. The Government responded by severely restricting the freedom of the press (1799), thus quelling a large part of the public debate. Chapter 2 Chapter 2 provides a survey of the national development from about 1800-1848 with particular reference to the Duchies. The starting-point was the involvement of the monarchy in the Napoleonic Wars (ab. 1801 -14). The war resulted in increasing taxation, which the big landowners protested against because they found they were hit particularly hard. They gathered round Frits Reventlow, who was the leader of the socalled » Knighthood«, the landed aristocracy. Reventlow’s fervent hope was the re-introduction of the Schleswig-Holstein regional parliament (which functioned until 1712), and in this line of thought he gained the support of a German historian, F.C. Dahlmann, who became secretary to the »Knighthood« in 1815. Dahlmann pinned his faith on the newly formed »German Federation« of all German states, whose aim was to reestablish the old German empire (dissolved in 1806). The problem was that the German Federation acknowledged Holstein as a member, but not Schleswig, which had not belonged to the German Empire. Dahlman, however, strongly advocated the right of the Schleswig-Holstein people to a shared constitution as historically endorsed by the shared regional parliament. In spite of all efforts Dahlmann had to give up this cause when his appeal to the German Federal Diet was rejected (1823). But his idea of a common constitution was taken up in 1830 by a young lawyer Uwe Jens Lomsen who had been associated with the German Chancellery, and now represented politically liberal attitudes. According to his proposal Schlewig-Holstein was to have a common free constitution with a legislative and fiscal parliament, and the central administrative bodies were to be moved from Copenhagen to Kiel. These proposals were regarded as highly radical, but Frederik VI attempted to pour oil on the troubled waters by moderate reforms, as decreed in 1834: a Schleswig-Holstein joint government at Gottorp, a joint Schleswig-Holstein high court of justice, but, most important, four Assemblies of the Estates of the Realm, two for Jutland and the islands, and two for Schleswig-Holstein, all of which were to assemble every second year. The electoral rules favoured the landowners and the relatively well-to-do farmers, but it was Schleswig-Holstein lawyers and civil servants who came to dominate the proceedings of the Holstein as well as the Schleswig Assembly of the Estates as they had the majority behind them. In the first Assemblies of the Estates (1835-38), the mood was fairly peaceful, but the 1840s saw a decisive breakthrough for the Schleswig-Holsteiners. As late as in 1838 the majority in the Schleswig Assembly of the Estates were able to support a proposal for Danish as the judicial and administrative language in Northern Schleswig where Danish was used in church and schools, but in 1840, when the new King Christian VIII granted this wish with a »language ordinance«, it met with vehement resistance in the same assembly. At the next Assembly of the Estates in Schleswig in 1842 several Schleswig-Holsteiners directly repudiated United Monarchy symbols; in retaliation, the leader of a small Danish-minded group in the Assembly, P. Hiort Lorenzen, began to speak Danish in the Assembly in spite of strong protests from the chairman and the members. This episode came to have great importance. In the Kingdom, Hiort Lorenzen was praised and celebrated, not least by the Copenhagen Liberals who now broke with the Liberals in Kiel and became »National Liberals«. In Northern Schleswig Danish national feeling was strengthened, as it was most strikingly manifested at Skamlingsbanken wheremany thousand people, mostly Northern Schleswig farmers, gathered in 1843 and 1844. But the Schleswig-Holsteiners retaliated with whole series of meetings and rousing singing by large choirs. From 1844 they united round a »Regional Party« which, among other things, adopted the Augustenburg Duke’s claim to right of succession to the Duchies. When in 1846 Christian VIII rejected this claim in an »open letter«, anti-Danish feelings ran high. The Holstein Assembly of the Estates sent a protest to the German Federation, and both the Holstein and the Schleswig Assembly were disrupted as members resigned their seats. However, at the election in 1847 for the Assemblies of the Estates, pro-Danish attitudes saw great progress. Chapter 3 The debate on Dahlmann’s proposal for a constitution had not ceased when a new one began, initiated by Claus Harms' s criticism of the Rationalist tendencies in the Regional Church. At the time he was a newly appointed pastor at the University Church in Kiel, but worked almost as a reformer, especially in a treatise on Luther’s »95 Theses« (1817). As a preacher he attracted large crowds, not least professors and students, and Dahlmann composed an address of thanks to him. He achieved great importance for the students of theology with his pastoral-theological lectures in which he went through all the duties of a clergyman, and from the mid-1830s it came to be Harms’s pupils and sympathizers who dominated the Regional Church. In Harms’s opinion, all reforms should emanate from a cooperation among the clergymen, and the 1840s were actually a time of clerical conferences, which from 1845 were replaced by an annual »Predigerconferenz« for the whole of the Regional Church. The aim was to remove all traces of the Enlightenment theology in liturgy, catechism and hymn book, and finally to institute an independent constitution for the Church. Thus the reform movement came to represent a kind of ecclesiastical Schleswig- Holsteinism, but as a rule the Church dissociated itself from the political struggle. At least both Harms and his closest sympathizers retained a loyal relationship with authorities and the Danish King up to 1848. For the leading clergy, however it was natural to cooperate with the politicians and civil servants in Schleswig-Holstein. This was true not least of C.F. Callisen, Superintendent General to Schleswig from 1835. He was as loyal to the King as Harms was, but he did not conceal that he was working to develop the Regional Church into a »harmonious whole«, and that required, he believed, the exclusion of all Danish-educated clergymen and teachers! Another - related - example is the development in the deaneries of Tønder and Åbenrå, i.e. the southern part of Northern Schleswig. The language used in church and school was predominantly Danish, but in the 1830s two energetic deans, interested in the national aspect of the Church, came to the district. They were Mich. Ahlmann in Tønder and J.A. Retshof in Åbenrå, whose accounts are evidence in particular of an interest in the development of the teaching of German in the Regional schools. The pastors, too, became increasingly involved in national questions, and debates in the Schleswig Assembly of the Estates show that this was connected with the way pastors were employed in the two deaneries, namely through a vote in the congregation. In the northernmost part of Northern Schleswig pastors used to be appointed by the King, but in 1844 the Schleswig Assembly of the Estates agreed to propose that the system of employing pastors by vote should also comprise the deanery of Haderslev. Around the same time the clergymen began to fight against the Danish education of clergymen. As early as 1840, the majority of clergymen in the deaneries of Tønder and Åbenrå sent petitions to the Schleswig Assembly of Estates to request that Danisheducated clergymen should be excluded from employment. In 1844 the action was repeated with another collective petition, sharper in tone, from the same circles of clergymen. Thus the petitions had in reality united nearly all the clergymen in the two deaneries. Chapter 4 Like Claus Harms Grundtvig was at first known as an advocate of the old Lutheranism. However, Grundtvig was rather more inspired by the Church Service, the Sacraments and especially the Apostles’ Creed at Baptism. Here he found the evidence for the »historical-Christian faith«, and he advanced this »Church View« polemically against Rationalism in the booklet Kirkens Genmæle (The Church’s Retort), 1825. But unlike Harms’s Theses, this publication met with nearly unanimous condemnation among the clergy, and the result was that Grundtvig was sentenced for libel and became subject to censorship. About the same time he resigned his ministry and instead approached the Meeting Movement, a Danish layman Revivalist movement, and from 1832 he conducted a sort of voluntary meetings in Copenhagen. Not until 1839 did he get another ministry in Copenhagen. This situation led to a different view of the State Church. As early as 1827 he strongly advocated freedom of religion, his argument being that both the State and the official Church must be regarded as secularized, but through freedom of religion the »old-fashioned believers« could at least ga-ther under free-congregation forms. Some years later his view of the State Church softens: it was only meant to be a framework encompassing different forms of faith, but could still be of use, how-ever, as a common moral and educational organization, embracing Rationalists as well as »old-fashioned believers«. Moreover, he found a new fundamental social element in the Danish-Nordic folk culture, in which he had been engaged in his youth. Romanticism had taught him to conceive of the people as a spiritual organism, and the Age of Enlightenment allowed him to lay great stress on the importance of cooperation for »the common good«. But it should not be overlooked that he still worked as a clergyman, and actually hoped that there would be a Christian as well as a folkelig (national and cultural) revival among the people. Actually, Grundtvig’s folkelig activity only attained its full scope with his folk high school writings and his speeches in the »Danish Society«. The point of departure was his 51 lectures on recent history which he gave in 1838. They made such a strong impression that he continued right away to establish his own society, the »Danish Society«. It included many unlettered participants, because Grundtvig wanted to address common people and tried out many different ways of approach. The speakers should show variety in content and form; they should not lecture, but open up dialogue; there should be a great deal of singing and festivity on national commemoration days. In the beginning it was mostly Grundtvig who did the speaking, and his subjects ranged from histo-rical topics to current issues, for example constitutional and educational questions and the importan-ce of the mother tongue. As a consequence, Grundtvig was much in demand as a speaker in other societies. To Grundtvig these meetings came to have a special value since they afforded an opportunity for him to try out the educational reforms which he envisioned in the folk high school writings. Thus they became fundamentally important for Grundtvigianism as a folkelig movement. Outside Copenhagen, Northern Schleswig became the first workshop for the Grundtvigian-/ø/-fø//g experiment. Grundtvig was not particularly interested himself in the Schleswig issues, and until 1840 they had been broached by Schleswig-Holsteiners, rather than by pro-Danish Northern Schleswigers. But at the University of Kiel he had an energetic devotee, a professor of Danish, who was keenly appreciative of his folkelig thinking. In the late 30s Christian Flor came into close con-tact with a small pro-Danish circle of people in Haderslev, led by the merchant P.C. Koch, who now became Flor’s closest collaborator as the editor of the first Danish and pro-Danish weekly magazine, the Dannevirke, from 1838. In the opinion of both Flor and Koch, the magazine was intended to be exciting reading for common people, and therefore covered a wide range of subjects. Something similar was true of the first gathering at Skamling in 1843, planned by Koch. Shortly after, the Schleswig Society was founded, which was managed and dominated by ordinary farmers, and which led to the establishment of the first Grundtvigian folk high school in Rødding in November 1944. According to reports, it was intended to offer free lectures on history, literature and agricul-ture, but also to provide space for »anything relating to life«. Such aims might indicate an influence from Grundtvig’s activities in the Danish Society, but there were other factors of significance for the Danish movement. By and large, it was predominant in the Northern and North-Western part of Northern Schleswig, though in different ways. The Eastern part belonged to the Deanery of Haderslev and thus to the Regional Church, but all the clergymen were appointed »under the Royal Seal« and most of them were Danish-educated (in Copenhagen). In the 1830s they were, if anything, nationally passive, but opposed to a Moravian-like layman movement. In the 1840s the picture was somewhat different since »the Royal Seal« also allowed some German-educated clergymen (from Kiel), who supported the petitions from the deaneries of Tønder and Åbenrå against Danish-educated clergymen. But it was from the farmers of the deanery that Danish sympathies got the most significant support. They had originally become politically »awakened« by the Institution of the Assemblies of the Estates, and had been complaining constantly to the Schleswig Assembly about the disregard of the interests of the farmers (1836,1838 and 1840). In continuation of this followed the language conflict: Civil servants should use the language of the people, and the languages should have equal position in the Assembly. On the long run, it was especially the farmers of the Haderslev area that took the lead. It was they who first rallied round the Schleswig Society (with app. 300 members out of a total of 500,1843-47) and later the last great Danish-Schleswig petition of the period (with 36 initiators out of a total of 56), which, in the spring of 1847, collected nearly 4.000 signatures. In the North-Western district the situation was different. The first great language petition (1840) met with widespread support; but while the national conflict flared up in the Haderslev Deanery, things calmed down in the North West. This was probably due to the fact, as one clergyman wrote, that the people in the West were less exposed to the Schleswig-Holstein pressure than »our Brethren to the East« (1843). Moreover, the whole of the North Western district, which comprised app. 25 parishes in mid-country Tøminglen and about 10 »enclave parishes« on the West Coast, belonged to the Diocese of Ribe and was thus within Danish church jurisdiction. Most clergymen were therefore Danish-educated and employed in accordance with Danish rules. It was more of a problem to Danish national feeling that many laymen were influenced by the Moravian Brethren in Christiansfeld and the Danish Meeting Movement. J. Wegener, the first principal of Rødding folk high school, felt he was surrounded by reluctant religious-pietistic peasants (1844), and in the same year, after a journey to the North-Western district, Chr. Flor wrote that »the pro-Danish Christian people in the West« were all but dead to the causes of language and nationality. But at that time a change was already under way. In the years 1835-43, ab. 10 young clergymen were appointed on the West Coast who were all more or less » Grundtvigian«, and therefore active in church matters as well as in the cultural life of the people. Some of them also established close contacts with Revivalist circles, for example the Mjolden pastor, L.D. Hass (1835-40), who was highly esteemed by the Meeting-Movement leader on Funen, Peter Larsen. Another Meeting Movement leader on Mors, Chr. Kold, even moved to Mjolden, where he became Hass’s friend and collaborator (1838). Both P. Larsen and Kold moved closer to Grundtvigianism, and in Mjolden Kold introduced meetings for young people with singing and readings, and even a celebration of the Institution of the Assemblies of the Estates on the pattern of the »Danish Society« In 1840 Kold and Hass issued a petition against changes in the church service rituals. It gathered 516 signatures from 9 parishes in North Western Schleswig, only two of which had changed the original, decidedly Grundtvigian introduction. These are just examples that might be supplemented with others from the following years. But they all point to an increasing influence from the Grundtvigian clergymen in North Western Schleswig. Chapter 5 Undoubtedly, the great conflict over the Schleswig-Holstein issue was expected by many Schleswig-Holsteiners. But, surprisingly, it was triggered by the French February Revolution in 1848, which spread rapidly to other countries, everywhere as national »uprisings« against the rulers. In Copenhagen as well as in Kiel and Rendsburg, large crowds gathered in late March, demanding a free constituion and national unification, in Copenhagen by a joint constitution for the Kingdom and all Schleswig, in Kiel by a constitution for Schleswig-Holstein, which was also to embrace all Schleswig, after it had joined the German Federation. Certainly, the Schleswig-Holsteiners went to extremes by immediately setting up a provisional government. Actually it was a declaration of war, which caused problems for many clergymen in Schleswig. Their oath of office put them under obligation to support the absolute power of the King, and the great majority of clergymen dissociated themselves from the provisional government, when in April 1848 (when Schleswig was occupied by Danish military) they were asked by a royal commission to make a statement to that effect. This also applied to Superintendent General C.F. Callisen, who declared that he would continue to act in accordance with his oath of office. In the face of these reactions, however, the provisional government had immediately claimed that it had only intervened because the will of the Sovereign was no longer »free«. It was not Kiel, but Copenhagen, which had rebelled by forcing the King to separate Schleswig from Holstein. It should be added that the royal commission also met with supporters of the provisional government, among them some of the most prominent clergymen in the Regional Church, above all the deans J.A. Rehhoff in Åbenrå and Nicolai Nielsen in the city of Schleswig. They were both known as competent deans and engaged in the national aspect of the Church, and Nielsen was the central figure in the Reformist movement of clergymen advocating Harms’s ideas. Nielsen’s answer was printed, and he then took it upon himself to explain to the Schleswig-Holstein soldiers how they were to understand their oath of allegiance to the King. Shortly after Callisen was replaced by Nielsen as Superintendent for Southern Schleswig and Rehhoff as Superintendent for Northern Schles-wig (July 3rd 1848). Harms, too, now gave his blessing to the Schleswig-Holsteiners by praching at the opening of the legislative »regional assembly« (August 15th 1848). On this occasion he defended the Schleswig-Holstein uprising as a necessary self-defence against an intruding robber. Thus Harms’s movement seemed to have united with the national. The military events in the spring of 1848 ended with a major Prussian advance, followed by an armistice on July 2nd 1848. After that there were prolonged negotiations about an interim government. There were several successive administrations, but by and large they continued along the same lines as the provisional government, apart from a Danish government for Als and Ærø. There was also a certain consolidation of the Schleswig-Holstein church government in Northern Schleswig, presumably due to Rehhoff s influence as Superintendent. Many livings fell vacant after the pro-Danish clergymen had been dismissed and had fled and also of course for other more »natural« reasons. There were 31 new appointments in the autum of 1848 and the spring of 1849. And new appointees were usually pro-Schleswig-Holsteiners and German-educated men, often quite young. In May 1849 the government incorporated Töminglen into the Regional Church. There were other signs of a radicalization; in June 1849 even demands to break with the King and abandon the theory of the Duke as deprived of his freedom. But at that time a new political situation had arisen. The conservative Prussia no longer wanted to support the Schleswig-Holsteiners, but effected a new, more neutral armistice on July lCfh 18491 Schleswig was to be governed by a Prussian and a Danish civil servant, B.H. Eulenburg and F.F. Tillisch with an English diplomat as a mediator. Northern Schleswig was to be occupied by Swedish-Norwegian troops, Southern Schleswig by Prussian military, but the Schleswig-Holstein government and army were to be withdrawn into Holstein. The Schleswig-Holsteiners retaliated with fierce protests, organized by the clergy, especially Superintendent Nie. Nielsen and his close sympathizers in and around the city of Schleswig, as »passive resistance«. Already on August 22nd 1849 (a few days before the armistice came into effect) they proclaimed that they would continue to regard the Schleswig-Holstein government as their lawful authority, not the armistice commission. This statement was signed by the great majority of clergymen in Southern and Northern Schleswig. The conservative church circles in Berlin, however, dissociated themselves from this policy, a fact that was no doubt known to the leading Schleswig-Holstein clergymen, and they decided to counter this situation with a series of defensive writings. As early as September-October 1849, the first series came out, written by Mich. Baumgarten, a young clergyman in the city of Schleswig. Baumgarten began his series with a powerful appeal to civil servants to defend the »God-given« rights of the Land, which were now threatened by »our friends in Berlin«. After all, »our movement« had sprung from the civil servants who were now duty-bound to stand firm and show that Schleswig could not be governed by the armistice commission. Shortly after he found a concrete point of attack, as the commission had cancelled the provisional government’s church prayer for ’’»our Prince«. A church prayer for the King was an unjustified political tribute. He wrote a long pamphlet about this, and on the day it was published (October 10th) he agreed with a clergymen’s conference about a new petition against the abolition of the provisional form of government. The debate on this question provoked yet another petition against the clergymen having to announce proclamations from the commission (October 17th). Both petitions gathered many signatures, most, however from Southern Schleswig. It was obviously the clergymen in Southern Schleswig who took the lead in the »passive resistance«, and who were behind local petitions, and they did not refrain from heavy-handed demonstrations, for example against envoys from the armistice commission. Already in the autumn of 1849 the resistance was so extensive that the commission had to give up here. Chapter 6 Northern Schleswig Revival during the War As mentioned before, a pro-Danish movement had arisen among the rural population of Northern Schleswig, but until 1848 a certain conservatism prevailed in the majority of the people. Nationally it manifested itself only in loyalty to the King and to the centuryold feeling of affiliation with the Kingdom as well as Schleswig. But the Schleswig-Holstein uprising immediately provoked a widespread countermovement in the rural population of Northern Schleswig with popular mass meetings, addresses of tribute to the King and people taking up arms on a large scale. For example 2.000 farmers in the Ribe area are supposed to have been armed already on March 28th, and a few weeks later this peasant army co-vered the whole of the West Coast area up to Møgeltønder. There was a similar development in oi^e region, after the other - as far as one can judge from the fairly inaccurate information available. The movement was led by local personalities, especially the leading figures in the Schleswig Society. Several pro-German civil servants were harrassed or arrested , and a petition to the King on April 20th (possibly written by L. Skau) directly addressed the »powerful civil servant aristocracy« as oppressors of the farmers. Civil servants should be elected directly by the people! But the move-ment was supported by Chr. Flor and several clergymen, for example three who spoke at a military meeting in Skærbæk on March 30th, preparing the way for another meeting, held on April 7th, which agreed to send an address of confidence to the King. It was signed by the clergymen and 1.300 laymen in 11 South Western parishes, most of which had been nationally passive. The people’s army ceased to play a military role when around May l sl Northern Schleswig was occupied by Prussian troops. Thus the Schleswig-Holstein civil servants regained their importance. Some tried to gain the rural population’s favour, for example a grammar school teacher who pub-lished a new paper in Danish, the Nordslesvigske Tidende. It gave assurances that the Schleswig-Holsteiners did not want to oppress the farmers or the Danish language (May 6th). Others were clearly anti-Danish, such as the new Superintendent Rehhoff who blamed the pro-Danish clergy-men for the wavering attitudes of the population as well as for having caused people to take up arms which - according to Rehhof - was evidence of Godlessness and Communism. There exists a detailed account of the national development, written by a pro- Danish clergyman, Jep Hansen, ab. February 1849, and some main features from this description will be mentioned here. Before the War, he writes, the rural population in Åbenrå County had been »very quiet« and undecided; but the harsh behaviour of the Schleswig-Holsteiners had aroused resistance, and in Hjordkær the majority had taken Jep Hansen’s advice though he himself had to flee. After that, popular resistance spread rapidly in the area. This opinion is supported by another petition which was signed by many thousand people in Eastern Schleswig in October-November 1848. To this may be added another estimate, which appeared in the Nordslesvigske Tidende on March 17th 1949, signed by all the civil servants of Northern Schleswig. It is particularly remarkable in its extensive evidence of people’s Danish sympathies, causing them to send their conscripts to the Danish army, and to join the people’s army themselves. Several similar examples must be passed over here, but the conclusion of the civil servants should be indicated: it was the common people’s blind faith in authorities and their ignorance which had made them an easy prey for pro-Danish clergymen and teachers. But they would eventually yield to superior power and quieten down after »Germany’s peace with Denmark«. In correspondence with this attitude the Schleswig-Holstein government began to pursue a very strict policy from the autumn of 1848, particularly by enforced collection of taxes and hounding conscripts. This continued until the second armistice (July 10th 1849), which meant a great relief for the pro-Danish population. The Schleswig-Holstein regime was replaced by a commission, whose permanent members were a Prussian and a Danish civil servant, B.H. Eulenbrug and F.F.Tillisch .Töminglen was restored to the Diocese of Ribe, the refugees could return home, and the Danish newspapers came out again. The commission gave up intervening in Southern Schleswig, but it could not avoid taking a position on the dismissal of clergymen before the second armistice as those dismissed applied for reemployment. Not until November 1849 did Tillisch obtain approval of a few re-employments in cases where the dismissals were unjustified, and in January 1850, 7 people were dismissed becuase of disobedience to the commission. More dismissals followed on the same grounds, among them the two Superintendents, Rehhoff and Nic.Nielsen. The population of Northern Schleswig was highly involved in the conflict about the appointments to various posts, which was the principal subject of the Danish-language newspapers and at nume-rous parish meetings. In the late spring, however, everybody’s interest concentrated on the expected resumption of the war. Prussia made peace on July 2nd 1850, and the armistice came to an end on July 13th. To all intents and purposes the war was decided already on July 25th, when the Schleswig-Holstein main force suffered a defeat. However, F.F. Tillisch, who got nearly unrestricted power over the whole of Schleswig after the war, could continue to settle the score with the Schleswig-Holstein civil servants. According to the Kirchen- und Schulblatt, April 5th 1851, the commission and Tillisch are supposed to have ousted ab. 100 Schleswig clergymen by then, to which number should be added an equally large number of civil servants and a little more than half as many teachers. These figures have later been disputed by more recent investigations, but there can be no doubt that the number of dismissals was enormous. The figures of the Kirchenund Schulblatt are, however, interesting in themselves as the background of the German attacks in the following decades on the Danish administration of the Duchy of Schleswig.